Resettlement and state farm in central Ethiopia: analyzing the Dhaadallee-Harroollee resettlements and the Ethio-Yemen state farm (1974–1991) - Hailu Gelana Erko; Tesema Ta’a Wayessa; Tsegaye Zeleke Tuffa (Cogent Arts & Humanities)
This study analyzes state-led resettlement initiatives and agricultural reforms in central Ethiopia during the Derg regime (1974–1991), focusing on the Dhaadallee-Harroollee settlements and the Ethio-Yemen state farm. It investigates the demographic, socioeconomic, and environmental impacts of these policies. Utilizing qualitative data from oral histories, archival records, and existing literature, the research reveals systemic challenges that adversely affected the resettlement program. Despite the area’s rich potential for agriculture, agricultural productivity stagnated due to communal farming practices, resource scarcity, and settlers’ difficulties in adapting to new environments. Inexperienced labor, managerial inefficiencies, and recurrent labor shortages exacerbated low crop yields and food insecurity. The settlements also faced inadequate access to education, healthcare, clean water, and markets, compounded by endemic malaria. These deficiencies hindered sustainable livelihood development, despite the government’s attempts to mitigate them. Moreover, the Ethio-Yemen farm altered regional resettlement patterns, reflecting broader policy contradictions between centralized planning and local realities. The study, therefore, highlights how poor governance, agricultural support, and infrastructure inadequacies create vulnerabilities in Ethiopia. By examining these issues within the context of agrarian history, it contributes to discussions on forced migration and rural development, advocating for participatory and equity-focused resettlement policies.